Radial photovoltaic junction with single Si nanowire core–shell structure. (1st January 2015) - Dupré, Ludovic; Buttard, Denis; Solanki, A.; Pauc, Nicolas; Gentile, Pascal
Abstract : A single silicon nanowire core–shell structure has been elaborated. Technological stages of the process are presented. The device results in a P‐i‐N radial junction: the core is a P‐type silicon nanowire encapsulated in an intrinsic thin silicon layer and an N‐type doped silicon layer. Scanning electron microscopy observations, as well as the electrical I(V) characterisation on single nanowires, are presented.